PENINGKATAN HASIL BELAJAR PENDIDIKAN KEWARGANEGARAAN TENTANG NEGARA KESATUAN REPUBLIK INDONESIA (NKRI) MELALUI PEMBELAJARAN IMPROVE SISWA KELAS V SDN JETIS KECAMATAN JETIS PONOROGO - Sukmarto, Agung (Educatio Vitae, 2016)
This research aims to determine the study result of the elementary school  students to solve citizenship problem in terms of describing our country. The subject of this study is a student whoose improve their skill optimally for getting the best result for this lesson.the students were selected from fifth grade from jetis elementary school who  teached by the researcher. To determine the student whose improving their ability and describbing the NKRI,while to describe the thinking process of students in solving citizenship problems,the researcher held this research by using observation, reflection, place and planning in three cycle at sixth classmeeting, the researcher analyzed and interpreted the steps used by students with IMPROVE method. The result of this research indicated that the student can improving their ability to describing citizenship tended to use of  Introducing new concept, Metakognitif questioning, Practicing, Reviewing and reduding difficulty, Obtaining mastery Verification, Enrichment approaches. Key Words: Study Result, IMPROVE Method